2 The role of primary care in providing bereavement support: perspectives from a community sample. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Swash, Brooke; Thiemann, Pia; Newman, Rhiannon; Price, Annabel; Fraser, Derek; Barclay, Stephen
Abstract : Background: Around 5 00 000 people die in England and Wales each year, leaving approximately 2 million people experiencing close bereavement. Around 15% will develop a complex grief reaction requiring specialist support. GPs are often the first point of contact in the health services for bereavement support: GP consultations increase after a loss. GPs therefore have a central role in providing bereavement support and in identifying those at higher risk. Experiences and perceptions of primary care bereavement support are not well defined. Methods: Sixty three recently bereaved people were recruited via Registry Officers at the death registration appointment. A sub-sample of 14 participated in in-depth interviews within five months of bereavement, exploring their perceptions and experiences of primary care bereavement support. Audio recordings were transcribed verbatim, and analysed using a framework approach. Results: The nature of grief varied across the sample, shaped by prior losses, relationship with the deceased, and presence of sequential losses. GP support was one aspect of a broader picture of support provision. Barriers and facilitators of the use of primary care for bereavement support included: difficulty with securing appointments, prior relationships with the GP, the appropriateness of accessing general practice for a non-physical complaint, and expectations of how the GP might help. These served to either encourage or discourage potential help-seeking in bereavement. When the bereaved were registered at a different GP practice from one that had provided consistent GP palliative care for the deceased, bereavement care was particularly difficult. Discussion: Understanding bereaved peoples' perceptions of the role of the GP and the wider primary care team as a source of bereavement support, and the factors encouraging or discouraging such help-seeking in bereavement can enable primary care to optimise the provision of person-centred bereavement support.